Modelling of nonlinear behaviour of metallic structure components - Mirkovic, J. (Cranfield University, 2004)
Engineering has seen an increase in the use of computer simulations over experiments, in order to save time and reduce costs. The improvement of simulation tools continues with the objective of decreasing the difference between the results of numerical simulations and structural response in real mechanical processes. This study was focused on the improvement of simulation tools that will be used in aerospace crashworthiness, with the common type of problem defined as high-Velocity impact loading of thin-walled aluminium alloy structures. In order to achieve the defined task it was decided to develop a suitable material model that can provide the correct material response in the numerical simulations. The material model is developed as a part of the DYNA3D code and can be used for both solid and shell elements. Three phenomena that are essential for impact loading and that are incorporated in the material model are anisotropy, strain rate and temperature dependency, and material failure. The level of anisotropy that is treated is orthotropy which is a good approximation for sheet metal. For the purpose of providing more accurate results of dynamically loaded structures, a strain rate and temperature dependent flow stress definition was added to the material model. Based on the elastic-plastic algorithm with orthotropy and strain rate dependency, a tensile damage model was established. The current 3D damage/failure model is porosity based and allows for the modelling of tensile failure. The model can be applied to impact loading and both shell and solid elements. The performance of the developed material model was investigated by using a series of test cases, including helicopter impact on rigid surface, and the comparison of simulation results to experimental data. It was shown that the developed model provides improved material description in the simulation of aluminium alloys behaviour.